Relationship between Environmental Accounting and non-financial Firms Performance: An Empirical Analysis of Selected Firms Listed in Pakistan Stock Exchange, Pakistan - Ahmad, Muhammad; Waseer, Wasif Ali; Hussain, Shabbir; Ammara, Ume (Advances in Social Sciences Research Journal, 2018)
Environmental accounting provides a framework through measure present, past and future environment cost for decision-making and public communication. Environment awareness has made people concerned over the world in green accounting to observed ecological performance of their surroundings. The purpose of this study is to investigate relationship between environmental accounting and non-financial firm’s performance listed in Pakistan stock exchange, Pakistan. Present study used regression analysis technique (REM), using companies’ annual data from 2006-2016. The empirical analysis showed a significant positive relationship between environmental accounting and firm’s size. While, earning per share and return on capital employed statistically turned out to be insignificant. Therefore, those companies, which have huge size, spend more resources for social welfare in term of environment pollution protection. On the Contrary, the limitation of this research is small sample size of listed companies in Pakistan stock exchange. Hence, outcomes cannot be generalized for entire population. Based on the results, it is suggested that government must give some tax relief to those firms, which work for the environment protection and environmental reporting should be compulsory in Pakistan to have clean homeland. This study has contributed to literature by adding data from Pakistan. By the researcher’s best knowledge, the data on Pakistan is currently limited and this study contributes a better understanding on environmental reporting practices.